Workshop untuk Meningkatkan Kompetensi Guru SD dalam Implementasi Pendidikan Inklusif - Rosita, Tita (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2024)
The aim of this workshop is to improve the competency of State Elementary School teachers in implementing inclusive education. This activity uses the Service Learning (SL) method. Workshop activities were carried out at State Elementary School 106 Ajitunggal Cijambe Bandung with a sample of 40 elementary school teachers consisting of homeroom teachers and subject teachers. The workshop carried out in this service is carried out in three stages, namely (1) the stage of providing inclusive education material; (2). identification of students with special needs; (3). practice making profile reports of students with special needs; (4) post-training evaluation. The results of the workshop were that there was an increase in teacher competence at SDN 106 Ajitunggal, especially in the aspects of pedagogical competence and social competence. The pedagogical aspect of improvement includes teachers' understanding of the design of individual learning programs (PPI) for students with special needs and evaluation of their learning outcomes; Meanwhile, the aspect of increasing social competence includes teachers' understanding of how to communicate and interact effectively and efficiently with students with special needs and being able to communicate wisely to parents regarding the development of their children with special needs.